2010
DOI: 10.1007/s15010-009-9193-9
|View full text |Cite
|
Sign up to set email alerts
|

Nocardiosis: Updated Clinical Review and Experience at a Tertiary Center

Abstract: Nocardiosis is a rare opportunistic disease that affects mainly patients with deficient cell-mediated immunity, such as those with acquired immunodeficiency syndrome (AIDS) or transplant recipients. Pulmonary disease is the most common presentation in immunosuppressed patients and approximately one-third have a disseminated disease. Primary cutaneous nocardiosis is more frequently observed in immunocompetent patients with direct inoculation of the organism through professional exposure. The diagnosis can be ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
318
6
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(340 citation statements)
references
References 65 publications
5
318
6
11
Order By: Relevance
“…Increase in the infections caused by these organisms, with different clinical forms of systemic and disseminated forms of nocardiosis in transplant recipients, tuberculosis, liver cirrhosis, cancer, diabetes, AIDS and patients under treatment with immunosuppressive drugs and broad spectrum antibiotics in the world, reveals more importance of isolation and identification of these agents [2,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Various studies have shown that identification and isolation of these agents in soil of different areas help to diagnose nocardiosis [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Increase in the infections caused by these organisms, with different clinical forms of systemic and disseminated forms of nocardiosis in transplant recipients, tuberculosis, liver cirrhosis, cancer, diabetes, AIDS and patients under treatment with immunosuppressive drugs and broad spectrum antibiotics in the world, reveals more importance of isolation and identification of these agents [2,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Various studies have shown that identification and isolation of these agents in soil of different areas help to diagnose nocardiosis [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Deepseated soft tissue infection can occur by local traumatic inoculation or by haematogenous dissemination. In general, haematogenous dissemination was characteristic of immunocompromised hosts (Ambrosioni et al, 2010). Disseminated disease was present in four of the ten patients.…”
Section: Discussionmentioning
confidence: 86%
“…(Smego et al, 1983). The duration of therapy is variable and depends on the site of the lesions and the patient's immune status (Ambrosioni et al, 2010). If the CNS is involved, therapy must last for at least 12 months (Lerner, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…3 Typically, N asteroides results in pulmonary and disseminated disease, whereas N brasiliensis is more often associated with cutaneous and soft tissue infections. 4 Arthritis is a rare presentation of Nocardia infection. Most reported cases involve immunocompromised adults with disseminated disease or previously healthy people after a penetrating injury to the affected joint.…”
mentioning
confidence: 99%